Platelet-Rich Fibrin with β-Tricalcium Phosphate—A Noval Approach for Bone Augmentation in Chronic Periapical Lesion: A Case Report. (21st October 2012) - Jayalakshmi, K. B.; Agarwal, Shipra; Singh, M. P.; Vishwanath, B. T.; Krishna, Akash; Agrawal, Rohit
Abstract : Introduction . This paper describes a case of bone augmentation with combination of Platelet-Rich Fibrin (PRF) and β -TCP for treatment of chronic periapical cyst. The case was followed for 12 months. Methods . Patient presented with chronic periapical lesion in maxillary anterior teeth with history of trauma 8 years back. Radiographically, a periapical cyst was seen in relation to maxillary left central and lateral incisors. Conventional endodontic treatment was started. Since it was not successful, apical surgery was performed. Bone augmentation was done using PRF in combination with β -TCP bone graft to achieve faster healing of the periapical region. Regular followups at 3, 6, 9, and 12 months were done. Results . Healing was uneventful. Follow-up examinations revealed progressive, significant, and predictable clinical and radiographic bone regeneration/healing without any clinical symptoms. Conclusions . Combined use of PRF and β -TCP for bone augmentation in treatment of periapical defects is a potential treatment alternative for faster healing than using these biomaterials alone.